Applying English Video Learning Materials in Teaching Listening - Kamarullah Kamarullah; Asnawi Muslem; Abdul Manan (Universitas Syiah Kuala, 2018)
This study was designed to discover the use of English video learning materials in teaching listening to the second year students of the State Vocational High School (VHS) for Fishery of Ladong in 2018. The main goal of this study was to find out significant differences of the students’ listening achievement taught by applying the media (experimental group) and those taught with audiotape (control group). Each group selected, which was consisted of 24 students, brought the data through pre-test and post-test, which became as the research instrument. The result of which was then analyzed quantitatively. It was found that the mean score of the post-test of the experimental group (78.79) was higher than the mean score of the post-test of the control group (53.75). Moreover, both scores were analyzed by comparing ttest with ttable. The result of ttest was 8.44 while the ttable score at the level of significant degree α = 0.05 was 1.684. Therefore, the ttest score is higher than ttable (8.44 1.684). In other words, there was a significant difference in students’ listening achievement between the experimental and control groups. It can be taken into account that English video learning materials in listening class are helpful learning media.